Advancing Gender Equity in Health: The Role of Medical Women’s International Association - Wajiha Rizwan; Eleanor Nwadinobi (Journal of University College of Medicine and Dentistry)
This editorial highlights the key role of the Medical Women’s International Association (MWIA) and the Medical Women’s Association of Pakistan (MWAP) in advancing gender equity in healthcare. MWIA’s 2022-2025 theme, "One Humanity: Health Solutions through Our Partnerships," stresses the importance of collaboration to address gender inequities, particularly in low- and middle-income countries. Notable initiatives include the Equity 2030 Alliance with UNFPA, focusing on women-centric research, and the ‘Every Woman Treaty’ advocating for global standards to end violence against women. MWAP is working nationally to tackle workplace gender disparities through workshops and seminars aimed at creating harassment-free environments for women health professionals.Through strategic partnerships, MWIA and MWAP are promoting gender equity by fostering cross-sectoral collaboration and creating inclusive healthcare solutions. This editorial calls for global health professionals to unite in these efforts, ensuring accessible, equitable healthcare for all, regardless of gender.